Översättning av officiella texter och affärstexter från svenska till ryska och från ryska till svenska - Matytsina, Irina (Scandinavistica Vilnensis, 2014)
Transformation, understood very broadly, is the key word and the main method used in teaching Swedish to Russian speakers. As applied to official documents, it allows learners to see the peculiarities of business language in comparison with the neutral style.
Keywords: teaching Swedish to Russian speakers; Swedish business language